The Influence of Organizational Culture and Job Satisfaction on Organizational Citizenship Behavior (OCB) with Organizational Commitment as an Intervening Variable - Indiarto, Idward Resha; Wibowo, Imam; Guswandi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The increasingly dynamic world of education requires educators to exhibit Organizational Citizenship Behavior (OCB). OCB refers to voluntary behavior by employees who are willing to perform tasks beyond their formal obligations for the benefit of the organization. This study employs a quantitative descriptive approach. It was conducted at SDN Cakung Barat 04 Pagi, East Jakarta, with a population consisting of both educators and non-educational staff, and a sample of 52 respondents using a saturated sampling or census technique. The research aims to examine the influence of Variable X (Organizational Culture and Job Satisfaction) on Y (Organizational Citizenship Behavior, OCB) with Organizational Commitment as an intervening variable. Data analysis techniques include instrument testing (validity and reliability tests), descriptive analysis, SEM-PLS analysis, and simultaneous hypothesis testing (F-Test). The p-value for the influence of organizational culture on organizational commitment is 0.021. The p-value for the influence of job satisfaction on organizational commitment is 0.440. The p-value for the influence of organizational culture on OCB is 0.024. The p-value for the influence of job satisfaction on OCB is 0.034. The p-value for the influence of organizational commitment on OCB is 0.000. Organizational Culture influences Organizational Commitment, while Job Satisfaction does not. Organizational Culture, Job Satisfaction, and Organizational Commitment influence OCB. Organizational Culture influences OCB with Organizational Commitment as an intervening variable. Job Satisfaction does not influence OCB when Organizational Commitment is used as an intervening variable. Both Organizational Culture and Job Satisfaction influence Organizational Commitment. Both Organizational Culture and Job Satisfaction influence OCB